PRODUK PEMBIAYAAN PAKET MASA DEPAN BANK TABUNGAN PENSIUNAN NASIONAL (BTPN) SYARIAH TANPA JAMINAN - Ayu Franita Putri, Maria Ulfa KN (IAIN Tulungagung, 2020)
This research begins with the anxiety about the product of the National Islamic Pension Savings Bank using murabahah financing without using collateral. In general, financing carried out by Islamic banking requires a guarantee, but in practice in the National Islamic Pension Pension Bank there is no guarantee in financing. The case raises a new problem of collateral in murabaha financing. Issues discussed in this study are how financing at BTPN Syariah can be managed without collateral. This research uses the type of field research (field research) by using a juridical approach. The conclusion is that the financing of BTPN Syariah which provides an injection of funds to the community through a central coach to prosper the community at MMS Metro.The targetsare mothers to help their economy. In addition to the financing provided without the guarantee, mothers may make a financing loan with a payment system of every two weeks with the provisions of the profit sharing ratio of 30% of the terms of the initial agreement.